PENGARUH EDUKASI BATUK EFEKTIF TERHADAP KEMANDIRIAN ORANG TUA ANAK - Elmiana Bongga Linggi; Muh Ihsan Kamaruddin; Herlianty Herlianty; Darmi Arda; Suprapto Suprapto (Media Keperawatan:Politeknik Kesehatan Makassar, 2023)
Efforts to increase knowledge or understanding are with health education. Education is the process of not knowing about the value of health to knowing and from being unable to overcome one's health problems to be more independent.  Purpose of this study is to determine the effect of effective cough education on the independence of children's parents. The quantifiable research method with the design used quick experiments with pre-test research design and post-test design. The statistical test results showed that the value of knowledge before being given education was 19.56 in the measurement after being given education, an average value of 24.34 was obtained, with a variable knowledge value of P-Value: 0.000 and the independence of parents of children P Value: 0.027. The conclusion is that there is a difference between people's knowledge and independence for pre-test and posttest, so it can be concluded that effective cough education affects the knowledge of children's parents. There is an effect of effective cough education on the independence of children's parentsUpaya untuk meningkatkan pengetahuan atau pemahaman adalah dengan edukasi kesehatan. Edukasi sendiri merupakan proses tidak tahu tentang nilai kesehatan menjadi tahu dan dari tidak mampu mengatasi masalah kesehatan sendiri menjadi lebih mandiri. Tujuan penelitian ini mengetahui pengaruh edukasi batuk efektif terhadap kemandirian orang tua anak. Metode penelitian kuantitaif dengan desain yang digunakan quasy experiment dengan rancangan penelitian pre-test dan post-test design. Hasil Uji statistic menunjukan nilai pengetahuan sebelum diberikan edukasi adalah 19,56 pada pengukuran sesudah diberikan edukasi didapatkan nilai rata-rata 24,34, dengan variable pengetahuan nilai P-Value: 0,000 dan kemandiri orang tua anak nilai P Value: 0,027. Kesimpulan bahwa terdapat perbedaan antara pengetahuan dan kemandirian orang untuk pretest dan posttest, sehingga dapat disimpulkan bahwa ada pengaruh edukasi batuk efektif terhadap pengetahuan orang tua anak, dan terdapat pengaruh edukasi batuk efektif terhadap kemandirian orang tua anak